1994
DOI: 10.1159/000154217
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Enzyme and DNA Polymorphisms of Human Tissue-Specific Alkaline Phosphatases

Abstract: Enzyme and DNA polymorphisms and haplotypes of tissue-specific alkaline phosphatase genes were studied in Finns, Saamis and Swedes. In placental alkaline phosphatase (PLAP) restriction fragment length polymorphisms (RFLPs), found after digestion with RsaI and PstI, no significant population differences were observed. The PstI RFLP of the germ cell alkaline phosphatase (GCAP) locus showed significant allele frequency variations between Finns and Swedes (p = 0.014) and between Saamis and Swedes (p = 1 × 10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…DNA samples were collected from spontaneous abortuses from northern Sweden (n = 60) (Umeå Hospital region) and northern Finland (n = 45) (Uleåborg Hospital region). Control samples from these hospital regions were available from previous investigations [Beckman, 1970;Beckman et al, 1994]. DNA extracted from spontaneous abortion materials was analyzed by the SNuPE assay and frequencies of the D allele compared to control populations.…”
Section: Population Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA samples were collected from spontaneous abortuses from northern Sweden (n = 60) (Umeå Hospital region) and northern Finland (n = 45) (Uleåborg Hospital region). Control samples from these hospital regions were available from previous investigations [Beckman, 1970;Beckman et al, 1994]. DNA extracted from spontaneous abortion materials was analyzed by the SNuPE assay and frequencies of the D allele compared to control populations.…”
Section: Population Studiesmentioning
confidence: 99%
“…One of these rare alleles, D, was first thought to be restricted to Africans [Boyer, 1961] where it has been found at a frequency of about 0.8%. The D allele is apparently absent in Asian populations [Beckman, 1970] but has been found in most European ethnic groups, with the highest frequency (1.4%) found in Finns [Beckman et al, 1994]. Results from previous investigations have suggested that PLAP types of both the F and D alleles may be involved in intrauterine selection [G. Beckman and Beckman, 1975].…”
Section: Introductionmentioning
confidence: 99%
“…Other genetic variants which may contribute to susceptibility to EOP include polymorphic genes which encode other mediators of connective tissue homeostasis such as transforming growth factor-β, estrogen, alkaline phosphatase, type I collagen, and the transcription factor SP1. 12,41 Additionally, another polymorphism in the start codon of the VDR gene has recently been described and which also seems to correlate with BMD in different populations. 42,43 Several mediators of tissue inflammation also influence connective tissue turnover in particular in response to bacterial infection.…”
Section: Distribution Of Vdr Genotypes and Alleles Among L-eop Patienmentioning
confidence: 99%
“…The Saamis are a genetically unique population which has been found to differ from other Eu ropean populations in most examined marker systems including a Pst 1 RFLP in GCAP [17][18][19]. One notable exception is two RFLPs in PLAP [19].…”
Section: Resultsmentioning
confidence: 99%